Benthic algae stimulate leaf litter decomposition in detritus‐based headwater streams: a case of aquatic priming effect?. Issue 7 (1st July 2013) - Danger, Michael; Cornut, Julien; Chauvet, Eric; Chavez, Paola; Elger, Arnaud; Lecerf, Antoine
Abstract : In detritus‐based ecosystems, autochthonous primary production contributes very little to the detritus pool. Yet primary producers may still influence the functioning of these ecosystems through complex interactions with decomposers and detritivores. Recent studies have suggested that, in aquatic systems, small amounts of labile carbon (C) (e.g., producer exudates), could increase the mineralization of more recalcitrant organic‐matter pools (e.g., leaf litter). This process, called priming effect, should be exacerbated under low‐nutrient conditions and may alter the nature of interactions among microbial groups, from competition under low‐nutrient conditions to indirect mutualism under high‐nutrient conditions. Theoretical models further predict that primary producers may be competitively excluded when allochthonous C sources enter an ecosystem. In this study, the effects of a benthic diatom on aquatic hyphomycetes, bacteria, and leaf litter decomposition were investigated under two nutrient levels in a factorial microcosm experiment simulating detritus‐based, headwater stream ecosystems. Contrary to theoretical expectations, diatoms and decomposers were able to coexist under both nutrient conditions. Under low‐nutrient conditions, diatoms increased leaf litter decomposition rate by 20% compared to treatments where they were absent. No effect was observed under high‐nutrient conditions. The increase in leaf litter mineralization rate induced a positive feedback on diatom densities. We attribute these results to the priming effect of labile C exudates from primary producers. The presence of diatoms in combination with fungal decomposers also promoted decomposer diversity and, under low‐nutrient conditions, led to a significant decrease in leaf litter C:P ratio that could improve secondary production. Results from our microcosm experiment suggest new mechanisms by which primary producers may influence organic matter dynamics even in ecosystems where autochthonous primary production is low.